2015
DOI: 10.1371/journal.pone.0118889
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia-Ischemia and Therapeutic Hypothermia in the Neonatal Mouse Brain – A Longitudinal Study

Abstract: Therapeutic hypothermia is standard of care for infants with hypoxic ischemic encephalopathy. Murine models of hypoxic-ischemic injury exist; however, a well-established mouse model of therapeutic hypothermia following hypoxic-ischemic injury is lacking. The goal of this study was to develop a full-term-equivalent murine model of therapeutic hypothermia after hypoxia-ischemia and examine magnetic resonance imaging, behavior, and histology in a region and sex specific manner. Hypoxic-ischemic injury was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 59 publications
(48 reference statements)
8
78
1
Order By: Relevance
“…Others have tested different hypothermia temperature targets and some have found that there was no further neuroprotection (Weinrauch et al, 1992; Colbourne and Corbett, 1995), though some have found additional protective effect at 31 °C versus 34 °C in a neonatal rat model (Yager et al, 1993). Further, hypothermia in a similar neonatal model in mice has been observed to provide neuroprotection (as measured by MRI) and improved behavioral testing in males out to 20 days after ischemic injury, whereas the effect on females was variable and transient (Burnsed et al, 2015). A major difference between our findings and previous studies is the age of the rodents at the time of ischemia, as well as the mechanism of injury that is incurred.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Others have tested different hypothermia temperature targets and some have found that there was no further neuroprotection (Weinrauch et al, 1992; Colbourne and Corbett, 1995), though some have found additional protective effect at 31 °C versus 34 °C in a neonatal rat model (Yager et al, 1993). Further, hypothermia in a similar neonatal model in mice has been observed to provide neuroprotection (as measured by MRI) and improved behavioral testing in males out to 20 days after ischemic injury, whereas the effect on females was variable and transient (Burnsed et al, 2015). A major difference between our findings and previous studies is the age of the rodents at the time of ischemia, as well as the mechanism of injury that is incurred.…”
Section: Discussionmentioning
confidence: 98%
“…This may be particularly important in light of recent human studies showing lack of effect of hypothermia after out-of-hospital CA in children (Moler et al, 2015), suggesting a need for a better understanding through basic science. Further, it was also somewhat unexpected that there was a difference in the response to hypothermia in male and female juvenile mice, though questions regarding the depth of hypothermia have recently emerged from human trials (Nielsen et al, 2013) and previous reports have suggested sexually dimorphic responses in some behavior tasks in neonatal hypoxia–ischemia models (Burnsed et al, 2015; Smith et al, 2015). Lee and colleagues found that exposing neonatal male rats to 30 °C or 33 °C for varying lengths of time did not further reduce the loss of residual brain volume or motor behavior tasks one month after a model of neonatal hypoxic injury (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to 129Sv (HI resistance) and C57BL/6 mice (high mortality), CD1 mice display maximum neonatal HI brain injury with very low mortality rate (Sheldon et al , 1998). Adapting this model to the neonatal mice has also revealed that the duration of hypoxic exposure producing a moderate to severe injury in mice is significantly shorter (20–60 min) (Burnsed et al , 2015; Reinboth et al , 2016; Ten et al , 2004). …”
Section: Animal Models Of Neonatal Hi Brain Injurymentioning
confidence: 99%
“…Hypoxic ischemic (HI) encephalopathy remains the major cause of perinatal brain injury, resulting in short and long term disabilities (Burnsed et al, 2015; Chicha et al, 2014). It affects 60% of preterm infants and 1–8 cases per 1000 births (Vannucci, 2000).…”
Section: Introductionmentioning
confidence: 99%